2018
DOI: 10.21608/jppp.2018.41248
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Composite as a Dispenser for Methyl Eugunol to Attract the Peach Fruit Fly, Bactrocera zonata (Saunders) Males under Field Conditions

Abstract: Peach fruit fly (PFF), Bactrocera zonata (Saunders) (Diptera: Tephritidae) is considered one of the most economic important insect pest for several kinds of fruit species. Present work seeks to explore for the preparation of a novel composite based on petroleum coke with polyethylene, oleic acid and natural rubber as a dispenser for methyl eugunol. This target aims to get efficient dispenser composite to attract PFF males under field conditions in comparison with standard liquid lure dispenser (cotton wick). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Also, they found that paraffin oil gave more stability than sunflower oil to methyl eugenol with passed time. According to (El-Adly, et al, 2018 andElmetwally 2017), the efficacy of a novel composite as a dispenser for methyl eugenol to attract the peach fruit fly did not significantly affected by the time passed after hanging traps; while, methyl eugenol released from cotton wick dispenser significantly decreased gradually by the time.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they found that paraffin oil gave more stability than sunflower oil to methyl eugenol with passed time. According to (El-Adly, et al, 2018 andElmetwally 2017), the efficacy of a novel composite as a dispenser for methyl eugenol to attract the peach fruit fly did not significantly affected by the time passed after hanging traps; while, methyl eugenol released from cotton wick dispenser significantly decreased gradually by the time.…”
Section: Discussionmentioning
confidence: 99%
“…According to (El-Adly, et al, 2018) that efficacy of a novel composite as a dispenser for methyl eugenol to attract the peach fruit fly did not significantly affected by the time passed after hanging traps; while, ME released from cotton wick dispenser decreased significantly by the time passed. The present study revealed that the most stable treatment all over ten weeks wasmethyl eugenol75% diluted with oleic acid; where, , at a concentration of 75% exhibited approximately similar potentiality towards B. zonata adult males with time.…”
Section: In Mandarin Orchardsmentioning
confidence: 99%